Protecting my injured child: a qualitative study of parents' experience of caring for a child with a displaced distal radius fracture - E. E. Phelps; E. Tutton; M. L. Costa; J. Achten; A. Moscrop; D. C. Perry (BMC, 2022)
Abstract Background Childhood fractures can have a significant impact on the daily lives of families affecting children's normal activities and parent's work. Wrist fractures are the most common childhood fracture. The more serious wrist fractures, that can look visibly bent, are often treated with surgery to realign the bones; but this may not be necessary as bent bones straighten in growing children. The children's radius acute fracture fixation trial (CRAFFT) is a multicentre randomised trial of surgery versus a cast without surgery for displaced wrist fractures. Little is known about how families experience these wrist fractures and how they manage treatment uncertainty. This study aimed to understand families' experience of this injury and what it is like to be asked to include their child in a clinical trial. Methods Nineteen families (13 mothers, 7 fathers, 2 children) from across the UK participated in telephone interviews. Interviews were audio recorded, transcribed and analysed using reflexive thematic analysis. Results Our findings highlight parents' desire to be a good parent through the overarching theme "protecting my injured child". To protect their child after injury, parents endeavoured to make the right decisions about treatment and provide comfort to their child but they experienced ongoing worry about their child's recovery. Our findings show that parents felt responsible for the decision about their child's treatment and their child's recovery. They also reveal the extent to which parents worried about the look of their child's wrist and their need for reassurance that the wrist was healing. Conclusion Our findings show that protecting their child after injury can be challenging for parents who need support to make decisions about treatment and confidently facilitate their child's recovery. They also highlight the importance of providing information about treatments, acknowledging parents' concerns and their desire to do the right thing for their child, reassuring parents that their child's wrist will heal and ensuring parents understand what to expect as their child recovers.